Diagnosis and Management of Fingolimod-Associated Macular Edema - Wang, Chunjiang; Deng, Zhenzhen; Song, Liying; Sun, Wei; Zhao, Shaoli (Frontiers in Neurology, 2022)
Objective To investigate the clinical features, treatment, and prognosis of fingolimod-associated macular edema (FAME) and to provide a reference for its rational management. Methods FAME-related case reports were included in a pooled analysis by searching Chinese and English databases from 2010 to November 31, 2021. Results The median age of 41 patients was 50 years (range, 21, 67 years), of whom 32 were women. The median time to onset of FAME was 3 m (range.03, 120), and blurred vision (17 cases) and decreased vision (13 cases) were the most common complaints. A total of 55 eyes were involved in FAME, including the left eye (14 cases), right eye (10 cases), and both eyes (15 cases), of which 46 eyes had best-corrected visual acuity close to normal (20/12-20/60) and 8 eyes had moderate to severe visual impairment (20/80-20/500). Fundus examination in 23 patients showed macular edema (11 cases). Optical coherence tomography (OCT) in 39 patients mainly showed perifoveal cysts (24 cases), ME (23 cases), and foveal thickening (19 cases). Fundus fluorescein angiography (FFA) in 18 patients showed vascular leakage (11 cases). Complete resolution of ME occurred in 50 eyes and recovery of visual acuity occurred in 45 eyes at a median time of 2 m (range 0.25, 24) after discontinuation of fingolimod or administration of topical therapy. Conclusions Macular edema is a known complication of fingolimod. All patients using fingolimod require regular eye exams, especially those with a history of diabetes and uveitis and those undergoing cataract surgery.